BUDAYA SEKOLAH DAN ETIKA PROFESI: PENGUKURAN PEMBERDAYAAN SUMBER DAYA MANUSIA SEKOLAH DENGAN PENDEKATAN SOFT SYSTEM METHODOLOGY - Desi Eri Kusumaningrum; Raden Bambang Sumarsoso; Imam Gunawan (Universitas Negeri Malang, 2019)
Abstract: Professional ethics is something that teachers need to uphold in carrying out their profession. The application of professional ethics is rooted in school culture as an educational institution that upholds the values and norms of society. The hypothesis of this study is that there is a significant influence of school culture variables (X) on professional ethics (Y). To answer this hypothesis, then make this research use quantitative research. The instrument used to measure the research variables was a closed questionnaire, so respondents chose alternative answers provided. The respondents of this study consisted of 31 people, consisting of: 1 principal; 20 teachers; and 10 school administrators. The study was conducted at Junior High School An Nur, Bululawang, Malang Regency, East Java, Indonesia. Data analysis uses simple regression. Based on the results of data analysis, it was concluded that there was an influence of school culture (X) on professional ethics (Y), with a regression coefficient of 0.537. The formed regression equation is Ŷ = 28.923 + 0.43X. Keywords: school culture, professional ethics, soft systems methodology Abstrak: Etika profesi merupakan hal yang perlu dijunjung tinggi oleh para guru dalam melaksanakan tugas profesi guru. Penerapan etika profesi berakar pada budaya sekolah sebagai lembaga pendidikan yang menjunjung tinggi nilai dan norma kemasyarakat. Hipotesis penelitian ini adalah ada pengaruh yang signifikan variabel budaya sekolah (X) terhadap etika profesi (Y). Untuk menguji hipotesis tersebut, maka penelitian ini menggunakan rancangan penelitian kuantitatif. Instrumen yang digunakan untuk mengukur variabel penelitian adalah angket tertutup, sehingga responden memilih alternatif jawaban yang telah disediakan. Responden penelitian ini berjumlah 31 orang, terdiri dari: 1 orang kepala sekolah; 20 orang guru; dan 10 orang tenaga administrasi sekolah. Penelitian dilaksanakan di SMP An Nur Bululawang Malang Jawa Timur. Analisis data menggunakan regresi sederhana. Berdasarkan hasil analisis data disimpulkan ada pengaruh budaya sekolah (X) terhadap etika profesi (Y), dengan koefisien regresi 0,537. Persamaan regresi yang terbentuk adalah Ŷ = 28,923 + 0,43X. Kata kunci: budaya sekolah, etika profesi, soft system methodology